Cluster approach for auto segmentation of blast in acute leukimia blood slide images - N. H., Harun; Mohd Yusoff, Mashor, Prof. Dr.; H., Rosline (Springer-Verlag, 2011)
Link to publisher's homepage at http://www.springerlink.com